Human immunodeficiency virus and HBV co-infection: independent entities, together by coincidence? - Mathur, Ajay; Goyal, Laxmi Kant; Gupta, Arvind Kumar; Hooja, Nupur; Yadav, R. N. (International Journal of Advances in Medicine, 2019)
Background: To ascertain the prevalence of HBV among HIV-infected, treatment- naïve patients visiting a tertiary care centre in Jaipur, Rajasthan, India. Methods: An observation analytic study was done at a tertiary care centre affiliated to medical college with retrospective analysis of the hospital data of 30 calendar months. During this period routine diagnostic screening of HIV infection and HBV infection was offered to every suspected patient admitted in hospital and every pregnant woman visiting antenatal care clinic. Patients with documentary evidence of HIV infection and history of Hepatitis B vaccination in last 30 days are not screened for these infections at our centre. The HIV screening was done as per NACO guidelines. The HBV screening was done using commercially available enzyme linked immunosorbent assay kits (ELISA) for detection of surface antigen (HBsAg). Results: The study prevalence of HIV infection was 0.11% (40/35289). The prevalence was more in male (0.45%) than females (0.06%). HBV was not detected in any of the HIV positive patient in this study. The study prevalence of HIV among pregnant females was 0.05% (10/22026). Conclusions: In this study, prevalence of HIV infection was 0.11%. The study prevalence of HIV among pregnant females was 0.05%. Other than pregnant women, maximum positive cases (13/30, 43.33% positive cases) were in the age group of 25-34 years (sexually active group). No patient had HIV and HBV co-infection.